Cytosol Peroxiredoxin and Cell Surface Catalase Differentially Respond to H2O2 Stress in Aspergillus nidulans - Yunfeng Yan; Xiaofei Huang; Yao Zhou; Jingyi Li; Feiyun Liu; Xueying Li; Xiaotao Hu; Jing Wang; Lingyan Guo; Renning Liu; Naoki Takaya; Shengmin Zhou (MDPI AG, 2023)
Both catalase and peroxiredoxin show high activities of H2O2 decomposition and coexist in the same organism; however, their division of labor in defense against H2O2 is unclear. We focused on the major peroxiredoxin (PrxA) and catalase (CatB) in Aspergillus nidulans at different growth stages to discriminate their antioxidant roles. The dormant conidia lacking PrxA showed sensitivity to high concentrations of H2O2 (>100 mM), revealing that PrxA is one of the important antioxidants in dormant conidia. Once the conidia began to swell and germinate, or further develop to young hyphae (9 h to old age), PrxA-deficient cells (ΔprxA) did not survive on plates containing H2O2 concentrations higher than 1 mM, indicating that PrxA is an indispensable antioxidant in the early growth stage. During these early growth stages, absence of CatB did not affect fungal resistance to either high (>1 mM) or low (<1 mM) concentrations of H2O2. In the mature hyphae stage (24 h to old age), however, CatB fulfills the major antioxidant function, especially against high doses of H2O2. PrxA is constitutively expressed throughout the lifespan, whereas CatB levels are low in the early growth stage of the cells developing from swelling conidia to early growth hyphae, providing a molecular basis for their different contributions to H2O2 resistance in different growth stages. Further enzyme activity and cellular localization analysis indicated that CatB needs to be secreted to be functionalized, and this process is confined to the growth stage of mature hyphae. Our results revealed differences in effectiveness and timelines of two primary anti-H2O2 enzymes in fungus.